Solvent-Dependent Green Synthesis of ZnO Nanopowders Using Mitragyna speciosa Leaf Extract: Impact on Piezo-Photocatalytic and Antibacterial - Sanyen, Thanyapa; Songpanit, Maneerat; Kansaard, Thanaphon; Wirunchit, Supamas; Chutipaijit, Sutee; Ishihara, Keiichi N.; Okumura, Hideyuki; Pecharapa, Wisanu; Mekprasart, Wanichaya; Boonyarattanakalin, Kanokthip (My University, 2026)
ZnO nanopowders were synthesized via a solvent-mediated green route using Mitragyna speciosa Korth. leaf extract as reducing and stabilizing agents. Deionized water and methanol were employed to tailor the phytochemical composition of the extracts. The influence of extract concentration (5–20 mL) and solvent polarity on structural, morphological, and functional properties was systematically investigated. Structural analyses confirmed the formation of Zn-O bonds and a phase-pure hexagonal wurtzite ZnO without secondary phases. Surface morphology revealed solvent-dependent morphological evolution toward spherical shapes and reduced aggregation in the methanol-derived system. For antibacterial activity, green ZnO nanopowders demonstrated enhanced biocidal effects against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus, comparable to that of commercial ZnO nanoparticles. Enhanced piezo-photocatalytic degradation of rhodamine B was achieved under combined light and ultrasonic irradiation, with superior performance observed for methanol-derived ZnO. This enhancement is attributed to the synergistic interplay of solvent-induced defect states, reduced particle size, and piezoelectric field-driven charge separation. Scavenger analysis confirmed that superoxide radicals ((Formula presented.)) dominate the degradation pathway by green-synthesized ZnO nanopowders prepared from different solvent extracts. Thus, a correlation between solvent-mediated phytochemical environments and piezo-photocatalytic activity provides new insights for the design of sustainable, high-performance ZnO-based catalysts.
Keywords: antibacterial; green synthesis; Mitragyna speciosa; piezo-photocatalytic; zinc oxide